Mindfulness and Behaviour Therapy for Insomnia: An Assessment of Treatment Effect in a Sleep Disorders Clinic Population with Insomnia. Issue 1 (27th April 2021) - Peters, Allie; Reece, John; Meaklim, Hailey; Junge, Moira; Cunnington, David; Ong, Jason C.; Jackson, Mervyn; Greenwood, Kenneth Mark
Abstract: Insomnia is a common major health concern, which causes significant distress and disruption in a person's life. The objective of this paper was to evaluate a 6-week version of Mindfulness-Based Therapy for Insomnia (MBTI) in a sample of people attending a sleep disorders clinic with insomnia, including those with comorbidities. Thirty participants who met the DSM-IV-TR diagnosis of insomnia participated in a 6-week group intervention. Outcome measures were a daily sleep diary and actigraphy during pre-treatment and follow-up, along with subjective sleep outcomes collected at baseline, end-of-treatment, and 3-month follow-up. Trend analyses showed that MBTI was associated with a large decrease in insomnia severity ( p < .001), with indications of maintenance of treatment effect. There were significant improvements in objective sleep parameters, including sleep onset latency ( p = .005), sleep efficiency ( p = .033), and wake after sleep onset ( p = .018). Significant improvements in subjective sleep parameters were also observed for sleep efficiency ( p = .005) and wake after sleep onset ( p < .001). Overall, this study indicated that MBTI can be successfully delivered in a sleep disorders clinic environment, with evidence of treatment effect for both objective and subjective measures of sleep.